Correlation of interleukin 6 (IL-6) with estrogen and progesterone receptor expression in breast cancer patients - Chaloob, Amal K. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Multifunctional cytokines play important and only partially defined roles in mammary tumor development and progression. Normal human mammary epithelial cells constitutively produce interleukin 6(IL-6) and a non-secreted form of tumor necrosis factor. Transformation of mammary epithelial cells by different oncogenesis is frequently associated with alterations of cytokine/ growth factor production and responsiveness. Methods: We measured levels of 1L-6 in 84 females with breast cancer and examined their correlation with clinicopathological variables including stages of the disease and estrogen and progesterone receptor expression on tumor cell. Results: Our results revealed significantly higher serum IL-6 in breast cancer patients (12.98 pg/ml) compared to a healthy group (2.05pg/ml) (P<0.05) and a direct association with different clinical stages. And we found that expression of this cytokine was inversely associated with estrogen and progesterone receptor cells. Conclusion: Serum levels of IL-6 are highly elevated in breast cancer patients and correlate with tumor progression. Assay for serum levels IL-6 can be used as predictive non-invasive tests for tumor progression in breast cancer patients; also our data suggest that cytokine could be involved in the aggressiveness of ER-PR negative breast tumors. Expression of interleukin 6(IL-6) correlates with estrogen and progesterone receptor in breast cancer patients.